ANALISIS INDUSTRIROKOK KRETEK DI INDONESIA TAHUN 1976 - 2001 - Santosa, Purbayu Budi; Rifai, Bahtiar (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2005)
This research found that there is a positive significant relationship between concentration ratio and performance in cigarette industry but there is a negative no significant relationship between advertising behavioral and performance. These findings rather different to common SCP theory, especially in advertising behavioral and performance. The rationale behind these findings is advertising behavioral was not used as a product differentiation strategy or as a barrier to entry but as to increase concentration ratio. Anticigarette campaign in live style advertising supports this rationale. Another finding was a negative significant relationship between capital and performance. This finding completed labor-performance relationship argument with capital-performance relationship. However, the negative sign implicitly supported labor-intensive argument.